How do SMEs use support services during their internationalisation process: A comparative study of French traditional SMEs and INVs in Asia. (December 2019) - Belhoste, Nathalie; Bocquet, Rachel; Favre-Bonté, Véronique; Bally, Frédéric
This article integrates research on the internationalisation processes of small and medium sized enterprises (SMEs) and export assistance services to investigate how such firms use support services drawing upon a large, qualitative study of 32 French traditional SMEs and international new ventures (INVs) that have entered Asia. Our key contribution is to consider the time to internationalisation (gradual or rapid) and the stage of internationalisation (entrance or intensification) rather than export intensity alone, and to examine how support services can help SMEs internationalise. The identification of different configurations of uses leads to the development of theoretical propositions that extend existing models pertaining to support services and firm internationalisation. These findings have several important managerial implications for support services to target their offer more precisely to two types of SMEs; they also provide useful guidance for SMEs to determine which tailor-made offerings from private and public actors are most applicable to their internationalisation efforts.